2018
DOI: 10.1007/s40200-018-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/MyD88 -mediated CCL2 production by lipopolysaccharide (endotoxin): Implications for metabolic inflammation

Abstract: Background Obese human and mice were reported to have higher circularity endotoxin (LPS) levels as compared to their lean counter parts. The current study was aimed to reveal the molecular mechanisms underlying the LPS mediated induction of CCL2 in human monocytes/macrophages. Methods Human monocytic cell line THP-1, THP-1 cells derived macrophages and primary macrophages were treated with LPS and TNF-α (positive control). CCL2 expression was determined with real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…In theory, regarding the underlying dynamics of inflammatory effects upon ALI, LPS enters the body and is recognized by lipopolysaccharide-binding protein (LBP), and then binds to cluster of differentiation 14 (CD14) to form the LPS/LBP/CD14 complex, which can induce inflammation through multiple signal transduction pathways to ultimately release a large amount of inflammation factors. This release causes lung damage, of which TLR4/Myd88/NF-κB is one of the most critical pathways (31,32). Our results also indicated that PSPs decreased LPS-induced increases in mRNA expression of inflammatory factors, and of TLR4, Myd88, p-IKB-α/IKB-α and p-p65/p65 proteins in lung tissue.…”
Section: Discussionsupporting
confidence: 59%
“…In theory, regarding the underlying dynamics of inflammatory effects upon ALI, LPS enters the body and is recognized by lipopolysaccharide-binding protein (LBP), and then binds to cluster of differentiation 14 (CD14) to form the LPS/LBP/CD14 complex, which can induce inflammation through multiple signal transduction pathways to ultimately release a large amount of inflammation factors. This release causes lung damage, of which TLR4/Myd88/NF-κB is one of the most critical pathways (31,32). Our results also indicated that PSPs decreased LPS-induced increases in mRNA expression of inflammatory factors, and of TLR4, Myd88, p-IKB-α/IKB-α and p-p65/p65 proteins in lung tissue.…”
Section: Discussionsupporting
confidence: 59%
“…Some genes whose transcripts were elevated by burn injury in this study have been shown to cluster into well-characterised regulons. The TLR4/MyD88 regulon is known to regulate production of ROS, immunosuppression and chronic inflammation in response to lipopolysaccharide challenge via NOX4, ARG1 and CCL2, 50 52 three genes whose burn trauma-induced elevations were not reversed by nephrilin in the current study. One possible line of investigation suggested by this result is co-treatment of thermal insult with both nephrilin and a modifier of TLR4 signalling such as fenofibric acid.…”
Section: Discussionmentioning
confidence: 55%
“…TLR4 is known to trigger the inflammatory response by activating the NF-κB pathway, which leads to the production of inflammatory mediators [ 34 36 ]. Activated TLR4 subsequently transmits inflammatory signals through the adaptor protein MyD88 [ 37 , 38 ]. The MyD88-dependent signalling pathway activated NF-κB to induce the inflammatory cytokine TNF-α [ 39 ].…”
Section: Discussionmentioning
confidence: 99%